2021
DOI: 10.3390/brainsci11070926
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies, Anxiety and Depression in OCD and Schizophrenia: Changes during COVID-19

Abstract: Background: The main aim was to examine changes in coping strategies, anxiety and depression in obsessive–compulsive and schizophrenia patients during COVID-19, in addition to controlling the influence of intolerance to uncertainty and experiential avoidance. Method: The first time, the study comprised (15–30 April 2020) 293 patients, 113 of whom were diagnosed with obsessive–compulsive disorder, 61 with schizophrenia and 119 healthy controls, aged 13–77 years (M = 37.89, SD = 12.65). The second time (15–30 No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Nevertheless, some of the positive impacts (i.e. not having to leave home during the lockdown or meeting other people) might indeed reflect a tendency to avoid social interactions, as previously observed in individuals with schizophrenia during the pandemic ( Rosa-Alcázar et al, 2021 ). Karanci et al (2019) found that negative social interactions were an important source of burden for Turkish people with schizophrenia and that they cope with this by avoiding social contexts.…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, some of the positive impacts (i.e. not having to leave home during the lockdown or meeting other people) might indeed reflect a tendency to avoid social interactions, as previously observed in individuals with schizophrenia during the pandemic ( Rosa-Alcázar et al, 2021 ). Karanci et al (2019) found that negative social interactions were an important source of burden for Turkish people with schizophrenia and that they cope with this by avoiding social contexts.…”
Section: Discussionmentioning
confidence: 66%
“…15165 cases of community-dwelling patients with schizophrenia in this survey all had mild to severe anxiety and depression, which is supported by previous research. Compared to the control group, community-dwelling patients with schizophrenia experienced signi cantly higher scores in HADS-A and HADS-D during the covid-19 pandemic [14]. Moreover, 40.8% of community-dwelling patients with schizophrenia (n = 76) reported depression and 32.9% reported anxiety [15].…”
Section: Discussionmentioning
confidence: 92%
“…However, the report did not analyze anxiety and depressive symptoms separately in patients with schizophrenia during the outbreak. A Spanish study showed that compared to the control group, community-dwelling patients with schizophrenia (n = 42) experienced signi cantly higher scores in Hospital Anxiety and Depression Scale Anxiety (HADS-A) and Hospital Anxiety and Depression Scale Depression (HADS-D) during the COVID-19 pandemic [14]. Moreover, 40.8% of community-dwelling patients with schizophrenia (n = 76) reported depression and 32.9% reported anxiety [15].…”
Section: Introductionmentioning
confidence: 99%
“…Der Großteil der Studien beschreibt negative Auswirkungen der COVID-19-Pandemie auf das Leben von Menschen mit Schizophrenie [9][10][11][12][13][14][15][16][17]. Andere Studien konnten bei unterschiedlichen untersuchten Faktoren keine Verschlechterung feststellen [18][19][20][21].…”
Section: Was Ist Bereits Bekannt?unclassified